2008
DOI: 10.1113/jphysiol.2008.160960
|View full text |Cite
|
Sign up to set email alerts
|

The increase in pulmonary arterial pressure caused by hypoxia depends on iron status

Abstract: Hypoxia is a major cause of pulmonary hypertension. Gene expression activated by the transcription factor hypoxia-inducible factor (HIF) is central to this process. The oxygen-sensing iron-dependent dioxygenase enzymes that regulate HIF are highly sensitive to varying iron availability. It is unknown whether iron similarly influences the pulmonary vasculature. This human physiology study aimed to determine whether varying iron availability affects pulmonary arterial pressure and the pulmonary vascular response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
177
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(184 citation statements)
references
References 34 publications
5
177
1
1
Order By: Relevance
“…This interaction between iron, hypoxia and the pulmonary circulation is consistent with known effects of iron on the hypoxiainducible factor (HIF) family of transcription factors and involvement of HIF in regulating cardiopulmonary physiology [2][3][4]. Studies from several centres have subsequently confirmed a link between iron status and idiopathic pulmonary arterial hypertension, demonstrating that iron deficiency is unexpectedly common in this disease and independently worsens morbidity and mortality (recently reviewed by Rhodes et al [5]).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…This interaction between iron, hypoxia and the pulmonary circulation is consistent with known effects of iron on the hypoxiainducible factor (HIF) family of transcription factors and involvement of HIF in regulating cardiopulmonary physiology [2][3][4]. Studies from several centres have subsequently confirmed a link between iron status and idiopathic pulmonary arterial hypertension, demonstrating that iron deficiency is unexpectedly common in this disease and independently worsens morbidity and mortality (recently reviewed by Rhodes et al [5]).…”
supporting
confidence: 69%
“…We also studied patients with chronic mountain sickness over 1 month at high altitude and found that depletion of iron by venesection was associated with worsening pulmonary hypertension despite a large reduction in haematocrit (although this effect was not immediately reversed by subsequent iron infusions) [2]. This work was preceded by an 8-h laboratory study of healthy ironreplete volunteers in which the increase in pulmonary arterial pressure caused by hypoxia was blunted by prior intravenous infusion of iron sucrose (200 mg), while the pulmonary vascular response to hypoxia was enhanced by reduction of iron availability with desferrioxamine [3]. The dose of iron used in these studies is small relative to total body iron stores (approximately 4 g), and current intravenous formulations such as iron sucrose are very safe.…”
mentioning
confidence: 99%
“…It was recently reported that iron chelation promoted and iron infusion limited the increase in systolic pulmonary artery pressure resulting from exposure to acute hypoxia in 16 normal volunteers. 14 It has also been shown that iron depletion exacerbated the increase in systolic pulmonary artery pressure associated with high altitude hypoxia in 11 subjects and iron infusion ameliorated this increase in 22 subjects. 5 These observations pointed to the possibility that iron status may influence the expression of pulmonary hypertension in Chuvash polycythemia as well.…”
Section: Introductionmentioning
confidence: 99%
“…Under hypoxic conditions and at high altitude, ID resulted in an increase in pulmonary arterial pressure in otherwise healthy subjects. 24,25 This has been mainly attributed to stabilization and transcription of hypoxia-inducible factors linked to contraction, proliferation, and migration of pulmonary artery smooth muscle cells. [25][26][27] Another proposed concept is that (ID-induced) anemia may limit the conversion of nitrite to nitric oxide, thereby inhibiting the antiproliferative and vasodilatation effects of nitric oxide on the pulmonary vasculature.…”
Section: Iron and The Lungsmentioning
confidence: 99%